Simultaneous laparoscopic cholecystectomy with abdominoplasty - Ibrahim, Ahmed Abdel Monem (International Surgery Journal, 2017)
Background: The use of laparoscope in surgical removal of gall bladder became one of the most popular surgical procedures and abdominoplasty which was used from long time even during 1900, mostly done as a separate surgical procedure in our research we combined both procedures in the patients subjected to the study. Methods: Thirty-two patients presented to our hospital with abdominal wall laxity and symptomatic cholelithiasis. All of them wanted to undergo a cosmetic procedure (abdominoplasty) to reduce the abdominal wall laxity. They were also diagnosed to have cholelithiasis and had intermittent episodes of pain in the right upper quadrant of the abdomen. The ports for laparoscopic cholecystectomy were made in such a way that all the ports sites were under the elevated skin flap that was excised during abdominoplasty, and there was no scar in the upper abdomen. Results: The procedure was completed without leaving any tell-tale signs of laparoscopic cholecystectomy, and this led to a better cosmetic result from the patients’ point of view. Conclusions:On conclusion, we recommend asking for abdominal ultrasound examination for all patients coming for abdominoplasty especially following weight loss after surgery for morbid obesity even if the patient is asymptomatic. We recommend the use of the technique which we used for port placement as it is convenient, easy, and has no side effects on patients in comparison with other techniques.